S-Propargyl-Cysteine Attenuates Diabetic Cardiomyopathy in db/db Mice Through Activation of Cardiac Insulin Receptor Signaling - Li, Ye; Xie, Kui-Fang; Chang, Ya-Hong; Wang, Cheng; Chen, Ying; Wang, Ming-Jie; Zhu, Yi-Chun (Frontiers in Cardiovascular Medicine, 2021)
Background: Endogenous hydrogen sulfide (H2S) is emerging as a key signal molecule in the development of diabetic cardiomyopathy. The aim of this study was to explore the effect and underlying mechanism of S-propargyl-cysteine (SPRC), a novel modulator of endogenous H2S, on diabetic cardiomyopathy in db/db diabetic mice. Methods and Results: Vehicle or SPRC were orally administered to 8-month-old male db/db mice and their wild type littermate for 12 weeks. SPRC treatment ameliorated myocardial hypertrophy, fibrosis and cardiac systolic dysfunction assessed by histopathological examinations and echocardiography. The functional improvement by SPRC was accompanied by a reduction in myocardial lipid accumulation and ameliorated plasma lipid profiles. SPRC treatment improved glucose tolerance in db/db mice, with fasting blood glucose and peripheral insulin resistance remaining unchanged. Furthermore, insulin receptor signaling involving the phosphorylation of protein kinase B (Akt/PKB) and glycogen synthase kinase 3β (GSK3β) were elevated and activated by SPRC treatment. Primary neonatal mice cardiomyocytes were cultured to explore the mechanisms of SPRC on diabetic cardiomyopathy in vitro. Consistent with the results in vivo, SPRC not only up-regulated insulin receptor signaling pathway in cardiomyocytes in dose-dependent manner in the basal state, but also relieved the suppression of insulin receptor signaling induced by high concentrations of glucose and insulin. Furthermore, SPRC also enhanced the expression of glucose transporter 4 (GLUT4) and 3H glucose uptake in cardiomyocytes. Conclusions: In this study we found a novel beneficial effect of SPRC on diabetic cardiomyopathy, which was associated with activation of insulin receptor signaling. SPRC may be a promising medication for diabetic cardiomyopathy in type 2 diabetes mellitus patients.